2020
DOI: 10.9788/s43076-019-00009-y
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with social support and adaptation to the university: psychometric properties

Abstract: The objective of this study was to verify the psychometric properties of the Satisfaction Scale with Social Support and the Adaptation to Higher Education Questionnaire with scores of Brazilian university students. The participants were 300 students from various courses and periods, 150 of public universities and 150 of private universities. The collected data were examined in the structural equation modeling environment, submitted to confirmatory factor analysis, multi-group confirmatory factor analysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…reduce. Research by Rodríguez et al (2017), De Oliveira-Nunes et al (2020 and López-Angulo et al (2022) also confirmed that social support helps students adapt better to studying, limiting their intention to drop out of school. Teacher support was confirmed to have no impact on students' intention to leave school (β = -.021, p>0.05).…”
Section: Discussionmentioning
confidence: 88%
“…reduce. Research by Rodríguez et al (2017), De Oliveira-Nunes et al (2020 and López-Angulo et al (2022) also confirmed that social support helps students adapt better to studying, limiting their intention to drop out of school. Teacher support was confirmed to have no impact on students' intention to leave school (β = -.021, p>0.05).…”
Section: Discussionmentioning
confidence: 88%